KAJIAN PENGEMBANGAN PANGAN LOKAL BERBASIS PENGOLAHAN HASIL PERIKANAN DI KABUPATEN PELALAWAN RIAU - Sumarto '; Pareng Rengi (Berkala Perikanan Terubuk, 2013)
The research aims to develop a local food-based products in the fishprocessing of Pelalawan regency, where was knowing with the sources ofavailability of raw materials, processing centers know that can be developed,identify and characterize the product, and strategy development. This studied wasconducted with survey method, PRA analysis and SWOT analysis. Local foodprocessing activities fisheries sector as a whole has the potential to be developedmainly on the type of product smoked fish, dried shrimp and lomek dried product.That products become the flagship product was a type of smoked fish (selais,baung, and catfish) with centers of raw materials and refined products in theregion in Langgam. The main problem was that the technology which applied inthe processing of simple, raw material availability and limited productivity. Somestrategies can be applied in the development of improved productivity and qualityof fishery products, cooperation and partnership in marketing and capital,streamline the use of fishery production facilities and infrastructure, improvingtechnical quality and motivation of human resources (fish processing) to improvethe competitiveness of fishery products .Keywords: local, food-based, fish processing